Collaboration among Governments, Pesticide Operators, and Farmers in Regulating Pesticide Operations for Agricultural Product Safety - Jing Gong; Hongyan Du; Yong Sun (Agriculture, 2023)
The regulation of pesticide operations still faces numerous challenges and issues. Conflicts of interest and power struggles among the government, pesticide operators, and farmers are crucial factors that impact the effectiveness of regulation. To enhance efficiency and ensure the quality and safety of agricultural products through stakeholder cooperation, this paper presents a dynamic evolution model based on the theory of evolutionary games. The model incorporates the government, pesticide operators, and farmers and evaluates the stability and effectiveness of the stakeholder cooperation mechanism under different circumstances. The research findings indicate the following: The relationships between the government, pesticide-operating enterprises, and farmers are characterized by intricate dynamics of cooperation and competition, coordination and contradiction, reciprocity, and mutual detriment. The stability and effectiveness of the stakeholder cooperation mechanism vary depending on different parameters. Several factors influence the stability of the stakeholder cooperation mechanism, with regulatory supervision from the government, stringent penalties for non-compliant pesticide operations, and strong incentives for farmers’ oversight being the most significant. The stakeholder cooperation mechanism can establish an evolutionary stabilization strategy when these factors reach a certain threshold. This study contributes to understanding the operational mechanisms of stakeholder cooperation in pesticide operation regulation and offers decision support and policy recommendations to relevant stakeholders for advancing the sustainable development and optimization of pesticide operation regulation.